Take humidification filtering capability's room heater - WANG HUI (2017)
The utility model relates to a take humidification filtering capability's room heater, the casing is the square box body structure, its upper portion is the plenum, one side of plenum sets up the air outlet, the opposite side sets up the air intake, set up the filter screen on the air intake, be provided with fin and fan in the plenum, the fin is just to the air outlet, the intracavity is provided with the water heater in the casing, circulating pump and humidifier, the delivery port of water heater passes through the water inlet of circulating pump intercommunication fin, the return water mouth of the delivery port intercommunication water heater of backing, be provided with the filler on the water heater, the air outlet on the steam pipeline intercommunication plenum is passed through to the gas outlet of humidifier, set up the moisturizing mouth on the humidifier, the utility model discloses an add hot water through the water heater, then set up the fin on the air outlet of heater casing, hot water passes